Does internal cardiac massage play a role in ROSC after prolonged CPR ? : Our experience in a tertiary care hospital - Kamath, Manjunath R.; P., Krishna Prasad; Gopalakrishnan, M.; Kiran, Amith (Journal of Health and Allied Sciences NU, 2015)
Cardiopulmonary resuscitation (CPR) is a life-saving skill involving chest compressions & ventilation to pump oxygenated blood through the vital organs of the body. Among different techniques and devices for chest compression, no single method has been definitively shown to produce the best outcome and hence, direct comparisons between them are not possible. Internal cardiac massage is the manual squeezing of the heart through a surgical incision into the chest cavity, when the chest is already open for cardiac surgery. Unlike the usual cardiac arrest scenarios, internal cardiac massage is employed mostly in cardiothoracic surgical patients and will have more chance for survival and favorable neurologic outcomes across all durations of CPR. We describe two cases of return of spontaneous circulation (ROSC) after prolonged CPR with internal cardiac massage performed in hospital setting.
Keywords: Cardiopulmonary resuscitation (CPR); in-hospital cardiac arrest (IHCA); internal cardiac massage; return of spontaneous circulation (ROSC)